PENGARUH SISTEM PENGENDALIAN MANAJEMEN DAN KECERDASAN EMOSIONAL TERHADAP KINERJA STAFF ATC DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL PEMODERASI (Studi Kasus pada Perum LPPNPI AirNav Indonesia) - Fathul Huda Anjumi (AKT 15 UMY 397, 2015)
*397 The objective of this study is to analyze the effect of management control system and emotional intelligence on the performance of Air Traffic Controller (ATC) staffs with locus of control as a moderating variabel. This analysis used management control system and emotional intelligence as independent variables. The dependent variable is Performance of Air Traffic Controller. The samples used in this research was ATC staff who have minimal education of Diploma 1. The sample was taken based on purposive sampling method, and met the criteria of sample selection. Based on the deployment process 58 questionnaire obtained. Statistical method used in this study is moderating regression analysis for the statistical test of hypothesis testing and statistical t test. The analysis results based on the use of independent variables indicate that emotional intelligence hasa positive and significant impact on performance, while management control system does not have a significant effect on performance. Meanwhile of all the independent variables in moderation using locus of control provide a positive and significant results.